Arabic Dialects in the Holy Qur’an: A Phonetic, Syntactic, Morphological, and Semantic Study - frakis, mahamed (El Omda in Linguistics and Discourse Analysis, 2025)
Abstract : This study aims to highlight some facts about the Quranic readings through models of Quranic expressions, and to stand on the manifestations of those dialects, and the criterion of difference and diversity in the dialects of the Arabs. The nature of this research required that it come out in an introduction and two chapters. In the first, we gave an overview of the nature of the Arabic language, and the dialects before the revelation was revealed, and the dialects and their relationship to the seven letters. In the second, we talked about the vocal level: we studied in it the change of sounds between humming, facilitating, opening, tilting, diphthonging, and pronouncing; Then we moved on to the grammatical and morphological aspects to see the difference in the form of the word, its punctuation and its syntax, and finally we clarified in the semantic the multiple meanings of some of the words of the Holy Qur’an, and we finished the study with some results and facts. Among the most prominent results of this study: The Holy Qur’an is a discourse that takes into account the reality of pluralism. Therefore, these methods of pronunciation are opportunities to know the dialects of the Arabs that were spoken by the Qur’an and followed by the tongues of the tribes. The multiplicity of dialects in the Qur'anic Qur'an is the largest evidence of the close relationship between Arabic dialects and Qur'anic readings, which reflected aspects of their multiplicity and contrasting environments.